Artificial altitude training strategies: Is there a correlation between the haematological and physical performance parameters? - Fernández-Lázaro, D.; Mielgo Ayuso, J.; Caballero Garcia, A.; Pascual Fernández, J.; Córdova Martinez, A. (Archivos de medicina del deporte, 2020)
Introduction: Exposure to intermittent hypoxia (IHE) which is used as a complement to conventional training to obtain improvements in key haematological indices to increase athletic performance. Objective: We assessed hematological and physical performance changes by an IHE program in elite athletes (EA) living and training in moderate hypoxia. Material and method: For a 4-week normobaric IHE treatment (90 minutes, 7 days a week, 10-13 % FIO2) was applied at 12 EC. Their physical-anthropometric characteristics were established before the start of the study: Blood tests and physical tests were performed at 2 points in the study: a) on day 1, just before the start of the study (T1); b) on day 28, just at the end of the study (T2). The following were measured: reticulocytes (RET.), reticulocyte haemoglobin (Hb-RET ), erythropoietin (EPO), complete haematological profile and iron metabolism. Physical performance was determined by evaluation of aerobic potency, anaerobic potency, and velocity and maximum oxygen consumption (CsO2max). Results: Between T1 and T2 there is a significant increase in EPO, RET and Hb-RET, as well as a non-significant increase in the haematological variables involved in erythropoiesis HEM, Hb and Hcto. Performance increased in all physical tests, speed (1.96±2.35 %), aerobic power (3.73±5.34 %), CsO2max (3.36±4.35 %) and was significant in anaerobic power (p = 0.05 with 1.93±1.13 %). Conclusions: The IHE program of 4 weeks' duration in combination with training is able to stimulate hematological parameters such as EPO, RET, HEM, Hct, and Hb that demonstrate an activation of the erythropoiesis of the athlete and could be the cause of improvements in all performance tests, being only significant the increase in anaerobic potency.